88. A Behavioral Economic Approach to C. difficile Testing Stewardship. (31st December 2020) - Drees, Marci; Winiarz, Michael; Zhang, Zugui; Dressler, Robert; Eppes, Stephen C
Abstract: Background: To decrease inappropriate testing for C. difficile patients, we first employed an alert, followed by a hard stop (based on lack of documented diarrhea or laxative use), that could be overridden only by calling the laboratory. We describe a behavioral economic approach to test overrides that decreased the burden on both clinicians and laboratory staff without encouraging unnecessary testing. Methods: Our 2-hospital, > 1200-bed community-based academic healthcare system has performed PCR-only C. diff testing since January 2015. We implemented our initial laxative alert, which did not prohibit testing, in March 2015. In April 2017, we launched a "hard-stop" alert that cancelled orders without documented diarrhea or recent laxative use. The provider could override by calling the laboratory and documenting the laboratorian's name in the order; no further justification was required, but entries were intermittently monitored. In August 2019, we allowed clinicians to document their clinical justification instead of making this additional call, while emphasizing that rationales would be monitored for validity (Fig 1). We measured number of C. diff tests completed/month, overrides, and CDI standardized infection ratios (SIRs). We performed time-series analysis to account for each of these test ordering changes. Figure 1: Image of C. diff alert Results: At baseline, we observed a mean of 448 (SD, ±25) C. diff orders per month. The initial laxative alert led to a sustained decrease in monthly C. diff orders by 17% (p < 0.001; Fig 2). Another sustained decrease in monthly C. diff orders of an additional 29% (p< 0.001) occurred after the "hard stop" alert. Overall, C. diff orders decreased by 40% (3.5% per month). After introduction of the clinical justification documentation, to date we have not observed significant trends in C. diff override rates. The CDI SIR decreased from 0.9 (95% CI, 0.77- 1.04) in 2016 to 0.52 (0.42–0.64) in 2019. Figure 2: Interrupted time series analysis Conclusion: An iterative process to improve C. diff testing stewardship resulted in sustained improvements in C. diff ordering and hospital onset CDI cases. Behavioral economic approaches emphasizing the importance of clinical reasoning allowed us to reduce burden on clinicians and laboratory staff without increasing inappropriate testing. Disclosures: All Authors : No reported disclosures